Essai de typologie des greniers ruraux de Gaule du Nord - Alain Ferdière (Revue Archéologique du Centre de la France)
This paper was published in the proceedings of the AGER Symposium, Clermont-Ferrand, France (2014), following an oral intervention. It investigates the diversity of pastoral farm buildings in northern Gallic and Germanic provinces. In these areas, six different designs of granaries have been highlighted, built in wood, stone or combined materials. For each of these granary types, several examples of specific buildings for grain storage on production sites characteristic of the Roman period in these regions are described. Their storage capacities and their specific distribution are detailed.